2020
DOI: 10.1029/2019ms001958
|View full text |Cite
|
Sign up to set email alerts
|

Analog Forecasting of Extreme‐Causing Weather Patterns Using Deep Learning

Abstract: Numerical weather prediction models require ever‐growing computing time and resources but, still, have sometimes difficulties with predicting weather extremes. We introduce a data‐driven framework that is based on analog forecasting (prediction using past similar patterns) and employs a novel deep learning pattern‐recognition technique (capsule neural networks, CapsNets) and an impact‐based autolabeling strategy. Using data from a large‐ensemble fully coupled Earth system model, CapsNets are trained on midtrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 64 publications
3
113
0
Order By: Relevance
“…Here, we show the performance of CNNs for a problem that can be of practical importance: predicting the evolution of spatio-temporal climate/environmental patterns in the context of the cluster indices. Such cluster-based data-driven forecasting using machine learning methods or other techniques has been of rising interest in recent years 8,12,20,41 . Clustered precipitation or surface temperature patterns provide geographically cohesive regions of interest while clustered Z500 patterns often have connections with modes of climate variability.…”
Section: Incorrectly Classified Patterns While the Results Presented Inmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we show the performance of CNNs for a problem that can be of practical importance: predicting the evolution of spatio-temporal climate/environmental patterns in the context of the cluster indices. Such cluster-based data-driven forecasting using machine learning methods or other techniques has been of rising interest in recent years 8,12,20,41 . Clustered precipitation or surface temperature patterns provide geographically cohesive regions of interest while clustered Z500 patterns often have connections with modes of climate variability.…”
Section: Incorrectly Classified Patterns While the Results Presented Inmentioning
confidence: 99%
“…Note that here we attempt to predict Z500 only from knowing the earlier Z500 pattern. Including more variables, e.g., geopotential heights at other pressure levels, sea surface temperature, etc., might improve the prediction accuracy, especially at longer leads (see the discussion in Chattopadhyay et al 20 ). We leave this to future work.…”
Section: Incorrectly Classified Patterns While the Results Presented Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep NNs have also been used to identify extreme weather and climate patterns in observed and modeled atmospheric states [24,19,20], to predict extreme weather events [e.g., 15], and to provide operational guidance and risk assessment for severe weather [26]. [21] developed deep NNs to extract spatial patterns in precipitation from gridded atmospheric fields, while [6] showed that deep NNs can skillfully predict extreme heat patterns several days ahead with relatively minimal input information. Another machine-learning effort has focused on the improvement of physics parameterizations in GCMs for both weather forecasting and climate prediction [4,32].…”
Section: Introductionmentioning
confidence: 99%